Fostering Communication Skills : Project-Based Learning In An Independent Curriculum - Nastiti Ulil Azmi; Yasiroh; J. Priyanto Widodo (PT. Gudang Pustaka Cendekia, 2024)
This study explores the implementation of project-based learning (PBL) within the framework of the Independent Curriculum (Kurikulum Merdeka) to improve communication skills among fifth-grade students. Employing a qualitative approach, data was collected through interviews and observations at MI Ma’arif Ketegan-Tanggulangin. Findings of this research indicate that PBL effectively improves students’ communication skills, fostering active engagement, creativity, and collaboration in classroom projects. Teachers play a crucial role in designing and facilitating PBL activities aligned with curriculum themes. The study suggests active student participation, teacher training in PBL implementation, and further research on the long-term effects of PBL on communication skills and academic performance